Structured professional development for academic developers: A collaborative approach. Issue 1 (2nd January 2022) - O'Riordan, Fiona; O'Sullivan, Íde; Fitzpatrick, Mary; Keane, Margaret; McAvinia, Claire; Risquez, Angelica
ABSTRACT: This paper shares the experience of a group of academic developers' engagement in collaboratively working towards the completion of an online open-access professional development (PD) course designed to support higher education teachers to engage with a new professional development framework. Committee members of the Educational Developers in Ireland Network set out to complete the course as a demonstration of their commitment to their own PD and to experience the process with a view to becoming facilitators of the course. An auto-ethnographic approach was used to capture this experience, and findings demonstrate an inspiring alternative to PD that supports academic developers in the quest to legitimise and prioritise their own PD in the context of highly pressurised roles.